2014
DOI: 10.5665/sleep.3652
|View full text |Cite|
|
Sign up to set email alerts
|

The CaV2.3 R-Type Voltage-Gated Ca2+ Channel in Mouse Sleep Architecture

Abstract: Low-voltage activated CaV2.3 R-type Ca(2+) channels in the thalamocortical loop and extra-thalamocortical circuitries substantially regulate rodent sleep architecture thus representing a novel potential target for pharmacological treatment of sleep disorders in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…However, we observed an opposite effect [239]. Our sleep study in Ca v 2.3 -/- mice suggested that Ca v 2.3 VGCCs significantly modulate sleep parameters in rodents in a light-dark cycle dependent manner.…”
Section: Structure Function and Pharmacology Of Voltage-gated Ca2+ Cmentioning
confidence: 83%
“…However, we observed an opposite effect [239]. Our sleep study in Ca v 2.3 -/- mice suggested that Ca v 2.3 VGCCs significantly modulate sleep parameters in rodents in a light-dark cycle dependent manner.…”
Section: Structure Function and Pharmacology Of Voltage-gated Ca2+ Cmentioning
confidence: 83%
“…Therefore, the prolonged REM sleep episodes might be homeostatically regulated by abnormally maintained NREM sleep episodes and the reductions in the attempts to enter REM sleep. However, contributions to these results by other brain regions, including the mesopontine nuclei and hypothalamic nuclei [42], that regulate REM sleep cannot be completely excluded because these brain regions express low levels of PLCβ4 and send inputs to the thalamus [43]. Therefore, further studies are needed to fully understand the observed changes in the REM sleep states.…”
Section: Discussionmentioning
confidence: 99%
“…Ca v 2.3 +/− embryos (kindly provided by Richard J. Miller, Department of Neurobiology, Pharmacology and Physiology, The University of Chicago, Chicago, IL, [1]) were re-derived with C57BL/6J mice and maintained with random intra-strain mating obtaining all genotypes [2]. Exons 4–8 encoding the pore-lining domain neighboring transmembrane domains of Cacna1e were replaced with a neo-URA3 cassette via homologous recombination (Mouse Genome Informatics; MGI Ref.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Subsequently, lysis was stopped by heating the samples to 95 °C for 15 min. Following brief centrifugation (30 s, 20,000x g ), isolated genomic DNA was used for PCR [2].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation